Pemanfaatan Media Audio Visual Dalam Pembelajaran Fikih Pada Kelas V di MI Ma'arif Kaliputih Alian - Hasanah, Desilia Uswatun; Mujiono, Slamet (IAINU Kebumen, 2026)
This research aims to explain the process of using audio-visual media in class V fiqh learningat MI Ma'arif Kaliputih and determine the learning motivation of class V students in the Fiqhsubject at MI Ma'arif Kaliputih by utilizing audio-visual learning media. This research isqualitative research with a research design in the form of descriptive research. The datacollection techniques used were interviews and documentation. The data analysis techniquesused are Data Reduction, Data Presentation/Data Display, and Conclusion/verification. Theresults of this research are that audio visual media is applied by teachers in class V, studentscan understand the material being studied and eliminate students' boredom with active andinteresting learning. Apart from that, the Jurisprudence Teacher uses assessments, one of whichis the Pre Test and Post Test as a reference for student motivation. In using audio-visual mediain learning Islamic jurisprudence, the students' scores increased and many students scoredalmost perfect on the post test.